Histopathologic Assessment of Prostate Cancer Bone “Osteoblastic” Metastases - Roudier, Martine P (2008)
PURPOSE: Many patients with prostate cancer develop bone metastases that appear osteoblastic on radiographs, yet these patients have an elevated risk of fractures. The discrepancy between the radiological and clinical aspects of those events is not well understood. The purpose of this study was to better characterize the histopathology of bone processes in prostate cancer bone metastases. MATERIALS AND METHODS: Histomorphometry was used to evaluate multi-site bone biopsies in each of 12 patients who died with multiple bone metastases, 7 of whom had received bisphosphonate therapy. RESULTS: Bone histomorphometry revealed a wide spectrum of cancer-induced bone changes in different metastatic sites within individual patients, ranging from a pronounced osteodense to a pronounced osteopenic type. Each metastatic lesion was associated with various amounts of resorption. Decreased bone volume was seen in half of all biopsies. Osteodense lesions were largely composed of undermineralized woven bone, which increases frailty of the new bone. Interestingly, woven bone was produced by alkaline phosphatase spindle-shaped cells arising from the connective stroma surrounding tumor cells. Bone response generally was similar in both bisphosphonate-treated patients and those who did not receive bisphosphonate therapy. CONCLUSIONS: Despite the osteoblastic nature of bone metastases in prostate cancer, the osteolytic-osteopenic bone lesions found in each clinically osteoblastic patient may explain the frequent fractures observed in these patients. In addition, the finding that woven bone formed directly from the tumor stroma and not from the adjacent bone surface supports further research into the mechanisms of abnormal bone formation in prostate cancer bone metastases.